Health Behaviors of a Sample of Adolescents in Bandar Abbas, Iran - Aghamolaei, Teamur (Kowsar, 2013)
BACKGROUND: Health promotion for adolescents has become a research priority worldwide and life at school offers a good opportunity to establish health promoting behavior among this age group. OBJECTIVES: This study aimed to investigate health behaviors of a sample of adolescents in Bandar Abbas, Iran. MATERIALS AND METHODS: Totally, 410 students including 204 males and 206 females studying in grades 9 to 12 and aged between 15–18 years old were studied. The instruments used to collect data were a self administered demographic questionnaire and the scale of Adolescent Health Promotion (AHP). RESULTS: The mean age of participants was 16.5 (SD = 1.34) years. The mean score of Adolescent Health Promotion (AHP) scale was 64.8 (SD = 8.9) ranging from 34.3 to 89.9. Female students scored significantly higher for health-responsibility, life-appreciation, and stress-management than male students (P < 0.05). In contrast, male students scored higher scores on exercise behavior than female (P < 0.05). All dimensions of AHP scale except for nutrition behavior and social support was associated with gender and nutrition behavior was associated with age (P < 0.05). CONCLUSIONS: This study indicated that sedentary life style and physical inactivity is a common and serious problem among high school students of Bandar Abbas.